Empowering industry through energy auditing: a case study of savings and sustainability - Anoune, Kamal; Ghazi, Mohamed; Ghazouani, Mokhtar; Nasiri, Badr; Zebraoui, Otmane (Institute of Advanced Engineering and Science, 2024)
Conducting energy audits is pivotal in assessing industrial plant efficiency and formulating effective energy management plans. It identifies opportunities for efficient energy use, reducing costs and environmental impact. This study employs a techno-economic approach to analyze electricity cost reduction in an industrial facility. Through energy auditing, it explores economic benefits and improved energy quality, yielding favorable outcomes. Focused on a plastic derivative manufacturing plant, the study reveals critical audit findings. The main aim is to identify avenues for electric energy savings, cutting production costs, and enhancing product competitiveness. The audit involves a detailed analysis of consumption patterns, signal quality, and potential energy management strategies, culminating in a cost-cutting plan. The results of an economic assessment of the suggested energy-saving strategies, provide a comprehensive evaluation of their financial implications. It reveals significant cost reduction opportunities, estimating annual energy savings of 45,824.56, which represents a 23.68% decrease in expenses. These initiatives not only boost the plant's financial performance but also strengthen its competitive edge.